2016
DOI: 10.1002/jat.3320
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctane sulfonate (PFOS) impairs the proliferation of C17.2 neural stem cells via the downregulation of GSK‐3β/β‐catenin signaling

Abstract: The neurotoxic effects of perfluorooctane sulfonate (PFOS) have attracted significant research attention in recent years. In the present study, we investigated the impact of PFOS exposure on the physiology of neural stem cells (NSCs) in vitro. We showed that PFOS exposure markedly attenuated the proliferation of C17.2 neural stem cells in both dose- and time-dependent manners. Additionally, we found that PFOS decreased Ser9 phosphorylation of glycogen synthase kinase-3β (pSer9-GSK-3β), leading to the activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Previous studies showed that GSK-3β played a crucial role in regulating apoptosis of NSCs, and inhibition of GSK-3β conferred NSCs resistance to apoptotic stimulator [16–18]. Additionally, it was reported that miR-26a directly targeted the 3′-UTR of GSK-3β in human adipose-derived mesenchymal stem cells [19].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that GSK-3β played a crucial role in regulating apoptosis of NSCs, and inhibition of GSK-3β conferred NSCs resistance to apoptotic stimulator [16–18]. Additionally, it was reported that miR-26a directly targeted the 3′-UTR of GSK-3β in human adipose-derived mesenchymal stem cells [19].…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that GSK-3β is a pivotal regulator of apoptosis [17]. Inhibition of GSK-3β makes NSCs more resistant to apoptotic stimulators [16–18]. Interestingly, it is reported that miR-26a could directly target the 3′-UTR of GSK-3β in human adipose-derived mesenchymal stem cells [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these observations suggest that BFs and PFs interact in a complex way with the cell proliferative machinery; endocrine disruptors can affect proliferation in different ways. BPA shows a significant interaction on neural stem cell proliferation and differentiation in the rat via the Wnt/β-catenin signaling pathway (Tiwari et al 2015), while PFOS disturbs cell proliferation by activating the glycogen synthase kinase-3β with resultant downregulation of cellular β-catenin (Dong et al 2016); Pierozan et al have recently described that PFOS and PFOA deregulate cyclin D1, CDK6, p21, p53, p27, ERK 1/2, and p38 in breast epithelial cells and that the cell cycle alteration persists in unexposed daughter cells after one and two passages (Pierozan et al 2020); however, the EDs doses utilized in this study were above the normal range of exposure (10-μM PFOS and 100-μM PFOA), and the overall mechanisms through which BPs and PFs at lower concentration (similar to the current daily exposure of humans) may alter regulatory cell cycle proteins need to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…One idea suggests that neurotransmitters bind to receptors in the dominant neuron or cell membrane to complete the information transfer, which leads to increased excitability and neurotoxicity (Hallgren et al, 2015;Ishida et al, 2017). Another idea suggests that PFOS might cause neurotoxicity by affecting syn-aptic plasticity (Pinkas et al, 2010;Dong et al, 2016). Moreover, both in vivo and in vitro studies have reported apoptosis of neuronal cells induced by PFOS (Chen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%